Whole-exome Sequence Analysis Implicates Rare Il17REL Variants in Familial and Sporadic Inflammatory Bowel Disease. Issue 1 (January 2016) - Sasaki, Mark M.; Skol, Andrew D.; Hungate, Eric A.; Bao, Riyue; Huang, Lei; Kahn, Stacy A.; Allan, James M.; Brant, Steven R.; McGovern, Dermot P. B.; Peter, Inga; Silverberg, Mark S.; Cho, Judy H.; et al.
Abstract : Background: Rare variants (<1%) likely contribute significantly to risk for common diseases such as inflammatory bowel disease (IBD) in specific patient subsets, such as those with high familiality. They are, however, extraordinarily challenging to identify. Methods: To discover candidate rare variants associated with IBD, we performed whole-exome sequencing on 6 members of a pediatric-onset IBD family with multiple affected individuals. To determine whether the variants discovered in this family are also associated with nonfamilial IBD, we investigated their influence on disease in 2 large case–control (CC) series. Results: We identified 2 rare variants, rs142430606 and rs200958270, both in the established IBD-susceptibility gene IL17REL, carried by all 4 affected family members and their obligate carrier parents. We then demonstrated that both variants are associated with sporadic ulcerative colitis (UC) in 2 independent data sets. For UC in CC 1: rs142430606 (odds ratio [OR] = 2.99, P adj = 0.028; minor allele frequency [MAF]cases = 0.0063, MAFcontrols = 0.0021); rs200958270 (OR = 2.61, P adj = 0.082; MAFcases = 0.0045, MAFcontrols = 0.0017). For UC in CC 2: rs142430606 (OR = 1.94, P = 0.0056; MAFcases = 0.0071, MAFcontrols = 0.0045); rs200958270 (OR = 2.08, P = 0.0028; MAFcases = 0.0071, MAFcontrols = 0.0042). Conclusions: We discover in a family and replicate in 2 CC data sets 2 rare susceptibility variants for IBD, both in IL17REL . Our results illustrate that whole-exome sequencing performed on disease-enriched families to guide association testing can be an efficient strategy for the discovery of rare disease-associated variants. We speculate that rare variants identified in families and confirmed in the general population may be important modifiers of disease risk for patients with a family history, and that genetic testing of these variants may be warranted in this patient subset. Abstract : Article first published online 16 October 2015.Supplemental Digital Content is Available in the Text.